A qualitative study on stakeholders’ perception of child car safety and acceptability of selected interventions to improve child-passenger safety practices in Ibadan, Nigeria (2016)
Background: Child car-passenger safety practices remain low in Nigeria. Findings from the formative phase of a project to deliver an m-health intervention on child-passenger safety to mothers/caregivers attending selected child-immumzation clinics in Ibadan are presented in this paper. The aim of this study was to describe stakeholders’ awareness of child passenger safety measures; to determine the cost of child car seats and acceptability of interventions to improve child-passenger safety practices. Methods: Twenty-four key-informant interviews with traffic enforcement officers (four), physicians (five), and mothers of children (fifteen) ;and a market survey was conducted. Results: Physicians and traffic law enforcement officers were more knowledgeable about child passenger safety measures compared to mothers. Cost of infant seats ranged from N6, 000.00 - N36, 000.00 (USD27.9 - USD167.67) and toddler seats, N6, 000.00 - N81, 000.00 (USD27.95 - USD377.27). Acceptance of a mobile-phone intervention and its accompanying law enforcement was very high. Conclusions: Our findings suggest that an intervention to improve child-passenger safety practices using mobile technology is acceptable to stakeholders in the study area. The intervention should address caregivers’ misconceptions about current child passenger safety measures as this could further enhance compliance with these safety measures.